p-Phthaloyl Chloride-Grafted SF Induced Biomineralization of Hydroxyapatites - Liu, Chao; Chen, Guangmei; Li, Rong (Asian Journal of Chemistry, 2013)
In this paper, p-phthaloyl chloride (DB)-grafted SF films was employed to regulate the mineralization of hydroxyapatite in 1.5 × SBF (1.5 times of simulated body fluid) for 24 h at about 36.5 ºC. It was discussed that the content of DB influence on the structure and morphology of the apatite composites deposited on the SF films. The structure and morphology of the composite materials were investigated by Fourier transform infrared, inductively coupled plasma emission spectrometer, X-ray diffraction and scanning electron microscopy. The results showed that the inorganic phase of component mainly were hydroxyapatite and they were self-assembled on the organic matrix and a three-dimensional framework was formed on the SF films. Ca/P molar ratio in the surface of biocomposites could reached 1.66. And the apatite was similarity to hydroxyapatite in natural bone in both microstructure and composition.